In vitro combined toxicity of chromium, nickel and PAHS in human lung cells as support for mixtures risk assessment - Alves, Inês (2021)
Risk assessment of chemicals mainly relies on exposure to single chemicals and their hazardous effects, although the real scenario in occupational settings is more commonly characterized by exposure to chemi-cal mixtures. Chromium (Cr), Nickel (Ni), and Polycyclic Aromatic Hydrocarbons (PAHs) are often pre-sent in occupational settings, such as aeronautic industries, where workers are exposed primarily through inhalation. Considering that those substances are recognized lung carcinogens acting mainly by genotoxic mechanisms, it is likely that interactive effects occur, indicating that the risk from occupational exposure to these chemicals should be assessed as a mixture. Such issue is being addressed in the HBM4EU Initiati-ve, where a real scenario of occupational exposure has been studied. In order to provide support to the hazard assessment of the referred mixture, the present work aimed to evaluate the combined toxicity of Cr(VI), Ni, and benzo(a)pyrene (BaP), using a human lung cell line (A549 cells). MTT assay was performed for each individual chemical and a dose-response curve was esta-blished, enabling the determination of the IC50. The combined toxicity of the Cr and Ni mixture as well as that of Cr, Ni and BaP were determined comparatively to the single chemicals’ toxicity to ascertain whet-her additive effects or deviations from additivity towards synergism or antagonism was obtained. The results will be presented and discussed and are expected to contribute to the overall mixture’s risk asses-sment.